Lean Seis Sigmas aplicado no ramo logístico: estudo bibliográfico - Freitas, Joelene de Menezes de (2016)
It is known that organizations seek tools that enable the achievement of its objectives. The LeanSeisSigmas is a union of techniques that guarantee the quality of processes at the same time broadens the strategic vision of the company . Based on this approach , this study aims to show through a literature review , the junction of two methods, Lean and Six Sigma applications directed to the logistics field. Also check how this relationship can bring strategic and financial benefits to organizations.